Pengaruh Macam Bahan Organik terhadap Nilai pH, pH0, Retensi P dan P tersedia pada Andisol Asal Ciater - Apong Sandrawati; Teddy Marpaung; Rina Devnita; Yuliati Machfud; Mahfud Arifin (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACT High phosphate (P) retention is a major problem in Andisol that causes low phosphate availability. This study was conducted to determine the effect of various organic matters for pH0, P retention and available P on Andisol obtained from Ciater, West Java. Organic matters used in this experiment consisted of humic acid, straw compost, cow manure, goat manure and chicken manure. This experiment was conducted from April to September 2017 at Soil Physics Laboratory, Faculty of Agriculture, Padjadjaran University. The design used in this experiment was a non Factorial Completely Randomized Design (RAL) with eleven treatments and three replicates. The treatments were control, humic acid (2 ml and 4 ml), straw compost (5% and 10% of the soil weight), cow manure (5% and 10% of the soil weight), goat manure (5% and 10% of the soil weight) and chicken manure (5% and 10% of the soil weight). The result showed that humic acid and various types of organic matter incubated for 3 months decreased pH0 and P retention, improved available P, but decreased pH0 and P retention as well as a negligible increase in available P.Keywords: Andisol, incubation, Humic Acid, pH0, P Retention, available-P